The Effect of Individual Counseling with the Cognitive Behavior Approach in Reducing the Smoking Behavior of Students of SMP Negeri 6 Medan - Siregar, Taufik Abdullah; Lesmana, Gusman (Jurnal Riset Ilmu Pendidikan, 2023)
Smoking dependence behavior in adolescents can occur due to a lack of knowledge of adolescents about the dangers of smoking. The desire to smoke also often arises due to uncomfortable situations such as loneliness, confusion, cold, boredom, anger and stress. The research objective was to determine the effect of individual counseling with a cognitive behavior approach in reducing smoking behavior in students of SMP Negeri 6 Medan. Sampling technique with purposive sampling technique. To obtain definite and relatively fast data in collecting data or information, the researcher uses an instrument in the form of a questionnaire. Based on the above data regarding the effect of individual counseling with a cognitive behavior approach in reducing smoking behavior as many as 20 people as respondents with a total of 50 items after being tested for validity and reliability, there are 46 valid items. So that from the data analysis it has been proven that there is a significant relationship between students of SMP Negeri 6 Medan. This is indicated by the correlation obtained from the output display of the SPSS model summary showing the product moment (pearson) correlation of 0.953 with a mean value before 147.3750 and after service of 146.2500. This means that there is a significant reduction in student smoking behavior through the application of individual counseling services